2020
DOI: 10.1111/jopr.13214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Home Bleaching Agent on the Ion Elution of Different Esthetic Materials

Abstract: Purpose: To investigate the effect of a 16% carbamide peroxide home bleaching agent on the ion elution of different esthetic restorative materials and to determine if the released ions exceed the minimal risk levels. Materials and Methods: Ceramic materials comprising a low-fusing porcelain (Vita VM7), lithium disilicate glass-ceramics (IPS e.max Press and IPS e.max CAD), zirconium substructure materials (IPS e.max ZirCAD and Vita In-Ceram YZ for InLab), and ceromers (Estenia and Tescera ATL) were chosen. Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 27 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…The chemical degradation of dental ceramics in acidic media has been previously investigated. 7,8,[11][12][13][14]19 Milleding et al 12 reported that immersion in 4% acetic acid solution at 80 C for 18 hours increased the surface roughness of leucite ceramic, a finding that was corroborated by another study, in which organic acids were reported to negatively affect lithium disilicate and zirconia-reinforced lithium silicate ceramics. 8 In another study on the chemical degradation of dental ceramics, including a leucite glass-ceramic and an yttria-stabilized zirconia, oxide ceramics eluted significantly fewer ions than glass-ceramics, which was observed on a larger scale in the acidic medium.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…The chemical degradation of dental ceramics in acidic media has been previously investigated. 7,8,[11][12][13][14]19 Milleding et al 12 reported that immersion in 4% acetic acid solution at 80 C for 18 hours increased the surface roughness of leucite ceramic, a finding that was corroborated by another study, in which organic acids were reported to negatively affect lithium disilicate and zirconia-reinforced lithium silicate ceramics. 8 In another study on the chemical degradation of dental ceramics, including a leucite glass-ceramic and an yttria-stabilized zirconia, oxide ceramics eluted significantly fewer ions than glass-ceramics, which was observed on a larger scale in the acidic medium.…”
Section: Discussionmentioning
confidence: 80%
“…The minimal risk levels of these toxic ions have been specified in a previous study on the ion elution of different esthetic materials when subjected to a home bleaching agent. 7 Lower elution values for Al, Ca, K, Li, Na, P, and Zn ions than the minimal risk levels were reported, whereas Cu levels were above the threshold for certain materials, including zirconia. 7 In the present study, As, B, Be, Cd, Cr, Co, and Zn levels exceeded the stated thresholds for each material-firing pair, regardless of aging.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations